Antioxidant Capacity Determination of Complex Samples and Individual Phenolics - Multilateral Approach - Petrovic, Marija; Suznjevic, Desanka; Pastor, Ferenc; Veljovic, Mile; Pezo, Lato; Antic, Malisa; Gorjanovic, Stanislava (Combinatorial Chemistry & High Throughput Screening, 2016)
Antioxidant (AO) capacity of various medicinal plants extracts and phenolic compounds was assessed by the most widely used spectrophotometric assays such as ferric reducing antioxidant power (FRAP) and scavenging of 2,2-azino-bis-3-ethylbenzothiazoline-6-sulfonic acid (ABTS) and 2,2-diphenyl-1-picrylhydrazyl (DPPH). In addition, two direct current (DC) polarographic assays, one based on a decrease of anodic current of [Hg(O2H)(OH)] - HydroxoPerhydroxoMercury(II) Complex (HPMC) formation in alkaline solution of H2O2, at the potential of mercury dissolution and another recently developed Mercury Reduction Antioxidant Power (MRAP), based on a a decrease of cathodic current of Hg(II) reduction were employed. Percentage of both currents decrease was plotted versus the volume of gradually added complex samples or the amount of individual ones and the slopes of these plots were used to express AO capacity. Total phenolic content (TPC) of extracts was determined by Folin- Ciocalteu (FC) assay. Correlations between applied assays were calculated by regression analysis. Relative Antioxidant Capacity Index (RACI), calculated by assigning equal weight to all applied assays and Phenolic Antioxidant Coefficients (PAC), calculated as a ratio between particular AO capacity and TPC, were used to achieve more comprehensive comparison between analyzed samples, as well as applied assays.
Keywords: hydrogen peroxide